2004
DOI: 10.1111/j.1460-9568.2004.03095.x
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of dorsolateral striatum preserve outcome expectancy but disrupt habit formation in instrumental learning

Abstract: Habits are controlled by antecedent stimuli rather than by goal expectancy. Interval schedules of feedback have been shown to generate habits, as revealed by the insensitivity of behaviour acquired under this schedule to outcome devaluation treatments. Two experiments were conducted to assess the role of the dorsolateral striatum in habit learning. In Experiment 1, sham operated controls and rats with dorsolateral striatum lesions were trained to press a lever for sucrose under interval schedules. After traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

80
909
8
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,062 publications
(1,015 citation statements)
references
References 49 publications
80
909
8
1
Order By: Relevance
“…By arguing that goal-trackers are indeed more goal-directed, this suggests the involvement of goaldirected neural structures (Yin et al, 2004(Yin et al, , 2005O'Doherty et al, 2004;Killcross and Coutureau, 2003). In agreement, goal-trackers do seem to recruit cortical "top-down" regulation of their response to reward-cues (Flagel et al, 2011a).…”
Section: Goal-trackersmentioning
confidence: 89%
“…By arguing that goal-trackers are indeed more goal-directed, this suggests the involvement of goaldirected neural structures (Yin et al, 2004(Yin et al, , 2005O'Doherty et al, 2004;Killcross and Coutureau, 2003). In agreement, goal-trackers do seem to recruit cortical "top-down" regulation of their response to reward-cues (Flagel et al, 2011a).…”
Section: Goal-trackersmentioning
confidence: 89%
“…Habit learning is characterized by a transition from response-consequence associations that are flexible and sensitive to reinforcement devaluation, to stimulus-response associations that are less flexible and sensitive (e.g. [20]). Thus, the initial part of habit learning may mainly involve activity in the mesolimbic dopaminergic branch, while the established habit and the skilled execution of the motor sequence may mainly involve the nigrostriatal dopaminergic branch.…”
Section: Discussionmentioning
confidence: 99%
“…It may be argued that the present study is mainly concerned with acquisition, since the task was new and relatively short. On the other hand, animal model studies have indicated that operant learning rapidly become habitual when the contingency between the response and reinforcer is weakened by using interval schedules [20], as used in the present study. Hence, it might be speculated that the control group rapidly developed a habit, while this process was hampered in the ADHD group.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have investigated the contribution of adenosine signaling in sub-regions of the dorsal striatum, the dorsomedial striatum (DMS; equivalent to caudate nucleus) and the dorsolateral striatum (DLS; equivalent to putamen) to habitual-seeking behaviors. Notably, the DMS primarily regulates goal-directed (action-outcome) behavior, which is sensitive to outcome devaluation and instrumental learning, whereas the DLS is more involved in habit (stimulus-response) formation (Yin and Knowlton, 2006;Yin et al, 2004;Yu et al, 2009). Since ethanol appears to impair several striatal functions including reward evaluation, motor function and habit formation (Corbit et al, 2012), the behavioral associations of adenosine signaling in habit formation have been examined.…”
Section: A2ar Inhibition In the Dms And Goal Directed Drinkingmentioning
confidence: 99%
“…Recent studies demonstrate that two different dorsal striatum regions, the dorsomedial striatum (DMS) and dorsolateral striatum (DLS), play distinctive roles in behavior development (Yin and Knowlton, 2006;Yin et al, 2007;. Notably, the DMS primarily regulates goal directed (action-outcome) behavior, which is sensitive to outcome devaluation and instrumental learning, whereas the DLS is involved in habit formation (stimulus-response) Graybiel, 2008;Yin et al, 2004). The DMS (analogous to the caudate) is a part of the associative network, which is involved in 'working memory' and the anticipation of reward.…”
Section: Introductionmentioning
confidence: 99%